Intensification of marrubiin concentration by optimization of microwave-assisted (low CO2 yielding) extraction process for Marrubium vulgare using central composite design and antioxidant evaluation. (1st January 2017) - Mittal, Vineet; Nanda, Arun
Abstract: Context: Marrubium vulgare Linn (Lamiaceae) was generally extracted by conventional methods with low yield of marrubiin; these processes were not considered environment friendly. Objective: This study extracts the whole plant of M. vulgare by microwave assisted extraction (MAE) and optimizes the effect of various extraction parameters on the marrubiin yield by using Central Composite Design (CCD). Materials and methods: The selected medicinal plant was extracted using ethanol: water (1:1) as solvent by MAE. The plant material was also extracted using a Soxhlet and the various extracts were analyzed by HPTLC to quantify the marrubiin concentration. Results: The optimized conditions for the microwave-assisted extraction of selected medicinal plant was microwave power of 539 W, irradiation time of 373 s and solvent to drug ratio, 32 mL per g of the drug. The marrubiin concentration in MAE almost doubled relative to the traditional method (0.69 ± 0.08 to 1.35 ± 0.04%). The IC50 for DPPH was reduced to 66.28 ± 0.6 μg/mL as compared to conventional extract (84.14 ± 0.7 μg/mL). The scanning electron micrographs of the treated and untreated drug samples further support the results. Discussion and conclusion: The CCD can be successfully applied to optimize the extraction parameters (MAE) for M. vulgare . Moreover, in terms of environmental impact, the MAE technique could be assumed as a 'Green approach' because the MAE approach for extraction of plant released only 92.3 g of CO2 as compared to 3207.6 g CO2 using the Soxhlet method of extraction.